Low‐risk non‐muscle‐invasive bladder cancer: Further prognostic stratification into the "very‐low‐risk" group based on tumor size. (4th March 2019) - Lee, Alvin; Lee, Han Jie; Huang, Hong Hong; Ho, Henry; Chen, Kenneth
Abstract : Objective: To validate the significance of the entity of "very‐low‐risk" bladder cancer by analyzing the clinical outcomes of low‐risk bladder cancer when further stratified by tumor size. Methods: We accessed our prospectively maintained, single‐institution, electronic bladder cancer registry to extract the clinicopathological data of patients who were diagnosed with primary, solitary, Ta, low‐grade tumors that were <3 cm. Patients were divided into two prognostic groups based on tumor size (≤1.0 cm vs >1.0 cm). The survival data of the two groups were compared for recurrence, progression and mortality. Results: A total of 165 patients were followed up for a median period of 79 months (interquartile range 47–118 months). A total of 45% (75/165) of the study cohort had tumors that were ≤1.0 cm. Recurrences were found in 40% (66/165) of the study cohort. On Kaplan–Meier analysis, patients with tumor size ≤1.0 cm had significantly longer time to recurrence ( P  < 0.001, log–rank test). Using multivariate Cox modeling, only tumor size >1.0 cm was significantly associated with shorter time to recurrence (HR 2.54, 95% CI 1.35–4.77, P  = 0.004). Tumor size was not significantly associated with any differences in time to overall progression, muscle‐invasive progression or overall mortality ( P  = 0.108, P  = 0.362 and P  = 0.225, respectively, log–rank test). Conclusions: Low‐risk bladder cancer can be further stratified based on tumor size. Larger tumors (>1.0 cm) are significantly associated with shorter time to recurrence compared with smaller tumors (≤1.0 cm). However, there were no significant differences in the probability of developing disease progression or overall mortality between larger and smaller tumors.